PENGELOLAAN RECORD CENTER DI PT. ANGKASA PURA II (PERSERO), TANGERANG BANDAR UDARA SOEKARNO HATTA - , TSU MAYYA, Waluyo S.S, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The writing ofthe final report, entitled "Record CenterManagementinPTAngkasaPuraII(Persero) Soekarno-HattaAirport" is the result of data collection Field Work Practice sare held at PT. Angkasa Pura II Field Work Practice has the goal of knowing the condition and determine treatment center Record Center and constraints faced. The method usedin research, such as throughobservation, library research andinterviews. Observation of direct observation of the Records Center processing in PT. Angkasa Pura II Soekarno Hatta Airport. Literature studythat will reviewthe literaturein orderto answerthe problem formulation or collect information relevantto the topic ofthe writing of the final report. Interview is intended to supplement the data thatit is still not perfect and get more detailed information from expert speakers in the field. Conclusionsof the final reportthat theRecord CenterManagementin PT. AngkasaPuraII(AP II) in accordancewith theproceduresof archivalscience. Records center managementisdoneinPTAngkasaPuraIIis setin the Standard Operation Procedure is designed to facilitate and maximize employment. Record Center management in APII is by using the Record Center Information System or commonly called recisa software to keep track of where filesare stored. Qualified human resources and havingwork experienceis key Record Center which can be managed properly. Synergy between the three aforementioned Record Center make smanaging APII tersistem properly and neatly. Adequate human resources and quality system computerize makePT. Angkasa Pur aII has an excellent managemen tand systematic.